Flip and TILT: ideas for listening and speaking practice - McLean, Terence (My University, 2025)
The challenge that I have embraced is to develop learning activities for the students to tackle on the days on which I do not teach online. I sometimes get the students to do asynchronous work, about which they make online posts and/or bring notes to class on Monday for group discussion. This is where 'Flip and TILT' comes into play.
Keywords: flipped classroom; Transparency in Learning and Teaching (TILT); teaching methods